EMPOWERING YOUTH THROUGH PHYSICAL EDUCATION: EXPLORING THE IMPACT OF HEALTH EDUCATION ON LIFELONG FITNESS AND WELLNESS - Tanveer Ali; Vikas Saxena (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
Physical Education (PE) and Health Education (HE) are integral components of a holistic educational experience that aims to promote students’ overall well-being. This research paper explores the combined impact of PE and HE in fostering lifelong fitness and wellness, with a focus on developing healthy habits, physical fitness, and mental well-being among youth. By analyzing existing research and current practices, the paper demonstrates how integrating Health Education into Physical Education programs can empower students to make informed health decisions, establish sustainable fitness routines, and develop resilience. The findings highlight the significant role of PE and HE in shaping positive health behaviors that extend beyond school years, preparing students for long-term wellness. Additionally, the paper discusses challenges in curriculum design, teacher training, and the inclusivity of PE programs. Ultimately, this research emphasizes the importance of a comprehensive approach to health education in schools to support students' holistic development and lifelong health.